Empowerment and job satisfaction in university teachers: A theory of power in educational organizations. - Borrego, Yolanda; Orgambidez-Ramos, Alejandro; Mora-Jaureguialde, Begoña (Wiley, 2022)
While the importance of teacher job satisfaction is welldocumented, the processes and mechanisms by whicheducational institutions manage to influence the satisfac-tions of their members are not. Studies on the organiza-tional elements associated with satisfaction have focusedon isolated factors without the common umbrella of aconsolidated theoretical model. Based on Kanter's theoryof power in organizations, we aimed to analyze themediator role of psychological empowerment betweenstructural empowerment and job satisfaction in a sample of267 university teachers in southern Spain. A cross‐sectionalstudy was carried out, utilizing questionnaires for datacollection and convenience sampling. Percentile confidenceintervals, based on 5000 resamples, were calculated totest the mediation model. Results showed that a two‐wayeffect of structural empowerment on job satisfaction: adirect effect based on access to organizational resources ofpower and an indirect effect through the development ofpositive cognitions at work. Access to opportunities,resources, information, and support empower universityteachers psychologically, fostering their intrinsic motivationand increasing their job satisfaction, key elements forteaching quality in higher education.
Keywords: Profesores de universidad - Condiciones de trabajo; Universidades - Aspectos sociológicos; Sociología de las organizaciones; Empowerment; Higher education; Job satisfaction; Teachers; University